Management of late blight (Phytophthora infestans) of potato (Solanum tuberosum) through efficient spray schedule of fungicides in the north-eastern Himalayan region of India - DEY, UTPAL; SARKAR, SHATABHISA; SEHGAL, MUKESH; MAJUMDAR, SAIKAT; AWASTHI, DURGA PRASAD; ACHARYA, LICON KUMAR; DUTTA, PRANAB; CHANDER, SUBHASH; SAHA, RATAN KUMAR (The Indian Journal of Agricultural Sciences, 2024)
Phytophthora infestans (Mont.) de Bary, belongs to order Peronosporales is one of the most destructive phytopathogen causing late blight disease of potato (Solanum tuberosum L.). The disease symptoms appear on leaf, petiole, stem, and tubers at any stage of crop growth and may cause severe disease epidemics leading to complete defoliation and extensive yield loss. The field experiments were conducted during 2020–21 and 2021–22 at Chesrimai GP, Charilam block, Sepahijala, Tripura to find out the effective management strategies with fungicides to mitigate the losses caused by the devastating disease. The experiment was laid out in a randomized block design (RBD) in 3 replications with 8 treatments having different fungicides in different combinations for determining the best spray schedule against late bight disease. Results revealed that one spraying of Mancozeb 75% @0.25% at 35 days after sowing (DAS), second spraying of Cymoxanil 8% + Mancozeb 64% @0.25% at 42 DAS, and third spraying of Mancozeb 75% @0.25% at 49 DAS and fourth spraying of Cymoxanil 8% + Mancozeb 64% @ 0.25% at 56 DAS recorded the best performing treatment, with the least mean disease severity (10.54 and 7.30%), the least mean disease incidence (15.00 and 12.75%), the least coefficient of disease index (CODEX) value (1.58% and 0.93%), and highest tuber yield (21.27 and 21.68 t/ha) during 2020–21 and 2021–22, respectively. In addition, there were 26.6 and 27.7% increase in yield over control during 2020–21 and 2021–22, respectively and the pooled incremental cost benefit ratio (ICBR) of 1:16.09 was found to be highest among all other treatments. Efficient spray schedule of prophylactic/ preventive spray with contact fungicide followed by spraying with translaminar/systemic + contact fungicide can effectively manage the late blight disease of potato under field conditions.